Key drivers of biomedical innovation in cancer drug discovery - Margit A Huber; Norbert Kraut (EMBO Molecular Medicine)
Abstract Discovery and translational research has led to the identification of a series of “cancer drivers”—genes that, when mutated or otherwise misregulated, can drive malignancy. An increasing number of drugs that directly target such drivers have demonstrated activity in clinical trials and are shaping a new landscape for molecularly targeted cancer therapies. Such therapies rely on molecular and genetic diagnostic tests to detect the presence of a biomarker that predicts response. Here, we highlight some of the key discoveries bringing precision oncology to cancer patients. Large‐scale “omics” approaches as well as modern, hypothesis‐driven science in both academic and industry settings have significantly contributed to the field. Based on these insights, we discuss current challenges and how to foster future biomedical innovation in cancer drug discovery and development.